Kontrol Suhu Air Pada Boiler Dengan Energi Gas Metana - Serly Dwi Khurniawati; Budhy Setiawan (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2022)
Currently, there are many industries that use alternative energy, namely waste energy that is converted into electrical energy, one of which is in the garden sector. Cow dung waste is processed into electrical energy at the Biogas Power Plant, some power plants are usually located in high mountains, which have a low ambient temperature, in this case 21Â°C. For the purpose of increasing methane gas production, efforts to increase the temperature of the cigar liquid above the ambient temperature of 21Â°C are attempted by adding boiler water with energy from the rest of the flue gas Covered In-Ground Anaerobi Reaktor (CIGAR) itself a liquid above 21Â°C. In this case, the waste waste Covered In-Ground Anaerobi Reaktor (CIGAR) is covered with a small Covered In-Ground Anaerobi Reaktor (CIGAR), to accommodate the methane waste. The methane will be used as energy to heat the air which has an initial average (21Â°C). The result of the air match will go to the mixing tank. The setpoint value at the stove temperature is 150-200 Â°C and the setpoint value at the maximum air temperature is 55 Â°C. In the air heating process, when the setpoint value is reached, the microcontroller will instruct the relay to turn off the gas by closing the gas input valve. The gas pressure needed for heating in the water heating process is about 2.2 KPa with a small gas discharge depending on conditions Covered In-Ground Anaerobi Reaktor (CIGAR) in the field. As a result, the water obtained has an average air temperature of 24.2Â°C with an average air discharge of 2 mâ„s Ã— 379 .